Pengaruh Debt to Equity Ratio dan Return on Equity terhadap Harga Saham pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Antis I’niswatin; Radia Purbayati; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Thiss research aims to detrmine how much influence the Debt to Equity Ratio (DER) dan Return on Equity (ROE) on Stock Prices at Food and Beverage Sub Sector companies listed on the Indonesia Stock Exchange for the period 2013-2018. The sample used in this research were ten companies obtained based on purposive sampling technique. The data used in this study is panel data so that the data will be tested using the help of the Eviews 9 application and analysed using panel data multiple analysis. The results of this analysis indicate that DER partially has a negative and significant effect on stock prices and ROE partially has a positive and significant effect on stock prices. Meanwhile, simultaneously, DER and ROE have a joint influence on stock price of companies in the Food and Beverage Sub Sector for the 2013-2018 period.